1998
DOI: 10.1016/s0550-3213(98)00446-5
|View full text |Cite
|
Sign up to set email alerts
|

Particle creation in the marginally bound, self-similar collapse of inhomogeneous dust

Abstract: We consider the evaporation of the (shell focusing) naked singularity formed during the self-similar collapse of a marginally bound inhomogeneous dust cloud, in the geometric optics approximation. We show that, neglecting the back reaction of the spacetime, the radiation on I + tends to infinity as the Cauchy Horizon is approached. Two consequences can be expected from this result: (a) that the back reaction of spacetime will be large and eventually halt the formation of a naked singularity thus preserving the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 67 publications
2
57
0
Order By: Relevance
“…Hiscock, Williams and Eardley [17] showed the diverging energy flux in the self-similar collapse of a null dust and also calculated the expectation value of stress-energy tensor in its two-dimensional version. Barve et al [18] showed the diverging power of radiation in the self-similar collapse of a dust ball. They also calculated the expectation value of stress-energy tensor in its twodimensional version [19].…”
Section: Introductionmentioning
confidence: 99%
“…Hiscock, Williams and Eardley [17] showed the diverging energy flux in the self-similar collapse of a null dust and also calculated the expectation value of stress-energy tensor in its two-dimensional version. Barve et al [18] showed the diverging power of radiation in the self-similar collapse of a dust ball. They also calculated the expectation value of stress-energy tensor in its twodimensional version [19].…”
Section: Introductionmentioning
confidence: 99%
“…By a simple computation, we can show that A + 4 /A − 4 here is the quantity denoted by γ in Ref. [2]. Hence, we find that the basic property of the map around the singularity is maintained in this new calculation, which does not use any information about the geometry away from the first singular point.…”
Section: Self-similar Casementioning
confidence: 73%
“…This self-similar model was discussed in Ref. [2]. The evolution of the circumferential radius is given by…”
Section: Self-similar Casementioning
confidence: 97%
See 2 more Smart Citations